Unprecedented cell structure variation in multilayered alternating PS/PMMA foams. (10th December 2021) - Pang, Yongyan; Zhang, Xin; Guo, Bingjie; Wang, Zhijun; Fang, Wenxiang; Li, Jiang; Zheng, Wenge
Abstract: The objective of the present work was to study the cell structure variation in multilayered alternating polystyrene/poly(methyl methacrylate) (PS/PMMA) foams with the increase of the layer number. The multilayered PS/PMMA foams were prepared via the combination of the co-extrusion technique and the subsequent batch foaming process with carbon dioxide (CO2 ) as the foaming agent. Controlled with the layer-multiplying elements (LMEs) in the co-extrusion system, multilayered alternating PS/PMMA stacks with various layers (8, 16, 32, 64 and 128) were prepared. It is found that with the increase in layer number, three types of cell structures were observed: the alternating big-cell/small-cell layers, alternating foam/film layers, and the almost uniform cell structure. It is believed that the layer thickness is a crucial factor in governing the formation and hence the variation of the cell structure. For a higher layer thickness, the foaming of the adjacent PS and PMMA layers are independent on each other, thus generating the alternating big-cell/small-cell layers. For a relatively thin layer thickness, the probable gas transfer from the PMMA layers to PS layers during foaming would hinder the formation of the small cells in PMMA, thus bringing the alternating foam/film layers, i.e., bricklaying-like structure. For a very thin layer thickness, the heterogeneous cell nucleation induced by the incompatible interfaces would be favorable for formation of the uniform cell structure. Graphical abstract: Image 1 Highlights: PS and PMMA are used to prepare multilayered foams with bimodal cell distribution. Three types of cell structure are observed with increase of layer number. Layer thickness plays a crucial role in the unprecedented cell structure variation. This study enriches the features of bimodal cell structure and multilayered foams.